The research of magnetic field, its power characteristics, properties of materials of electrical devices with unclosed magnetic system - E. G. Andreeva; V. S. Plekhanova (Омский научный вестник)
The article is devoted to the research of magnetic fields and their power characteristics in electrotechnical devices with an unclosed magnetic system (magnetic core) of various design and function. The purpose of the research: the development of electrotechnical devices with various design of unclosed magnetic systems, their mathematical and simulation modeling, taking into account the magnetic properties of the materials used to improve the technical and economic and mass-dimensional indicators (energy efficiency). Research methods: Numerical solution of the magnetic field equations by the finite element method and simulation using ANSYS and ELCUT software products. The results of the investigation of the electrotechnical devices with an unclosed magnetic system of various design purposes, conducted for a long time, is the development of magnetic field concentrators and the creation of hybrid magnetic systems. Conclusion: the developed electrotechnical devices with unclosed magnetic core allow, due to its design and configuration of the magnetic field, to increase the power characteristics of the magnetic field, ponderomotive forces, technical and economic and operational properties of the devices.